Metformin effects on head and neck squamous carcinoma microenvironment: Window of opportunity trial. (10th February 2017) - Curry, Joseph; Johnson, Jennifer; Tassone, Patrick; Vidal, Marina Domingo; Menezes, Diana Whitaker; Sprandio, John; Mollaee, Mehri; Cotzia, Paolo; Birbe, Ruth; Lin, Zhao; Gill, Kurren; Duddy, Elizabeth; et al.
Abstract : Objective: The tumor microenvironment frequently displays abnormal cellular metabolism, which contributes to aggressive behavior. Metformin inhibits mitochondrial oxidative phosphorylation, altering metabolism. Though the mechanism is unclear, epidemiologic studies show an association between metformin use and improved outcomes in head and neck squamous cell carcinoma (HNSCC). We sought to determine if metformin alters metabolism and apoptosis in HNSCC tumors. Study Design: Window of opportunity trial of metformin between diagnostic biopsy and resection. Participants were patients with newly diagnosed HNSCC. Fifty patients were enrolled, and 39 completed a full‐treatment course. Metformin was titrated to standard diabetic dose (2, 000 mg/day) for a course of 9 or more days prior to surgery. Methods: Immunohistochemistry (IHC) for the metabolic markers caveolin‐1 (CAV1), B‐galactosidase (GALB), and monocarboxylate transporter 4 (MCT4), as well as the Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) apoptosis assay and Ki‐67 IHC, were performed in pre‐ and postmetformin specimens. Exploratory mass spectroscopy imaging (MSI) to assess lactate levels also was performed in three subjects. Results: Metformin was well tolerated. The average treatment course was 13.6 days. Posttreatment specimens showed a significant increase in stromal CAV1 ( P < 0.001) and GALB ( P < 0.005), as well as tumor cell apoptosis by TUNEL assay ( P < 0.001). There was no significant change in stromal MCT4 expression or proliferation measured by Ki67. Lactate levels in carcinoma cells were increased 2.4‐fold postmetformin ( P < 0.05), as measured by MSI. Conclusion: Metformin increases markers of reduced catabolism and increases senescence in stromal cells as well as carcinoma cell apoptosis. This study demonstrates that metformin modulates metabolism in the HNSCC microenvironment. Level of Evidence: 4. Laryngoscope, 127:1808–1815, 2017